STAT-MS determination of Cd, Pb, and Zn leached from turkish glazed ceramic tableware - Yaman, Mehmet; Buyukaslan, Esra (My University, 2013)
In the literature, slotted tube atom trap-atomic absorption spectrophotometry (STAT-AAS) has been successfully used for the determination of Cd and Pb at the ng g-1 levels. In the present study, color-decorated dinner-ware was exposed to different concentrations of acetic, citric, tartaric, and lactic acid as well as concentrated and 7-mol L -1 nitric acid and yogurt. The extracted Cd, Pb, and Zn concentrations were determined by STAT-FAAS. The experiments indicated that there were differences in migration of citric/tartaric and lactic acid into foods as compared with acetic acid due to the strength of acidity. It was found that some porcelain plates released Cd (up to 0.084 mg dm-2) and Pb (up to 4.140 mg dm-2) which is more than the FDA limit of concentrations allowed (0.07 mg dm-2 for Cd and 0.8 mg dm -2 for Pb) by using 4% acetic acid.